Modern standard Arabic. Verb clinic : Arabic language learning software. - American University in Cairo Press; American University in Cairo Press ([Cairo] : American University in Cairo Press, 2005)
Tutorial for conjugating and using vocab in modern Arabic.
Title from disc label.
System requirements: 233MHz Pentium based system; 32MB RAM; Windows 98 SE, ME, 2000 or XP; 30MB free hard disk space; 4X CD-ROM drive; 800 x 600 resolution with 16-bit color; sound card.
Keywords: Arabic language -- Study and teaching; Arabic language -- Verb